PREVALENCE AND RISK FACTORS OF VITAMIN B12 DEFICIENCY AMONG PATIENTS WITH TYPE II DIABETES ON METFORMIN: A STUDY FROM NORTHERN REGION OF UNITED ARAB EMIRATES - Shahwan, Moayad; Hassan, Nageeb; Noshi, Adel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: This study focused on the prevalence of Vitamin B12 deficiency in UAE patients with type 2 diabetes mellitus (T2DM) who were treated with or without metformin. Methods: A cross-sectional study was conducted on 213 patients having diabetes type II were randomly selected to be part of the study in Northern Regions of the UAE, from June 2014 to February 2015. The patients aged >45 years and who had taken metformin for at least 3 months were recruited with regular follow-up at the outpatient clinic. The patients were included in a survey after which they had their serum B12 levels measured. Serum B12 levels <150 pg/ml are defined as the B12 deficiency. Results: About 48% of diabetic patients had confirmed the B12 insufficiency through laboratory tests. The patients on metformin had statistically lower values of B12 (p=0.002). The majority of participants n (%) took metformin had neuropathy, hypertension, dyslipidemia, numbness or paresthesia, and depression, or mood changes 140 (70%), 183 (91.5%), 134 (67%), 136 (68%), 161 (80.5%), and 120 (60%), respectively. Conclusion: Our study shows that for the patients with T2DM, long-term treatment with metformin is associated with higher chances of developing Vitamin B12 deficiency. Clinicians should, therefore, recognize this significant element and should screen diabetics who are on metformin treatment for any B12 insufficiency, which may be hidden, especially patients coming with neurologic symptoms.